THE RESULTS OF THE RANKING OF THE FACTORS FOR ACHIEVING THE SURPRISE OF THE ACTIONS OF THE NATIONAL GUARD OF UKRAINE IN A SPECIAL OPERATION FOR NEUTRALIZING ILLEGAL ARMED FORMATIONS - Balan, М. І.; Kolianda, V. V.; Drobakha, G. А.; Babкоv, Yu. Р. (Honor and Law, 2019)
Using the methods of expert appraisal, the factors of achievement of suddenness of actions of the National Guard of Ukraine formations in a special operation for neutralizing illegal armed formations were ranked. The significance of these factors was assessed.